Proposed Marketing Strategy at PT. ABC Bandung Using Three V's Method - Siandi, Hendry Arie; Hariandja, Evo S (The Indonesian Journal of Business Administration, 2013)
Automotive Industry growth in Indonesia is quite phenomenal. Unit of cars being sold are increasing each year. The growth of automotive industry becomes an opportunity for automotive replacement market. However competition in replacement market is believed to be more intense each year. Many players are interested to take part in this industry. When competition gets intense, customers are getting demanding because availability of choices they have. Automotive replacement market’s customers are divided into two customers B2C and B2B customers. PT. ABC Bandung is a spare parts distribution company who serve automotive replacement market in Bandung Area. Customers of PT. ABC Bandung are believed to be more concern about easiness in doing business. Threats are emerge from company current situation and customers demand. Analysis on customer demand will be needed to keep company in the business by creating intimacy with customers. Three values method is the right method to find out customer’s need and lead to creation of STP. Better STP is guidance for company to build their marketing mix. This thesis will analyze customer’s needs through creation of three value method. Keywords: automotive, b2b, marketing mix, 3v